Radiographic Appearance and Root Resorption Caused by Ameloblastoma in pts attending Teaching Institute of Dentistry - Ruqqia Jehan, Muhammad Shoaib, Muhammad Ali, Javeria Afzal, Asif Noor, Muhammad Jamil, Mustafa Sajid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Odontogenic tumors represent the heterogeneous organization of lesions with numerous histopathological characteristics and medical manifestations. Ameloblastoma is real neoplasm of odontogenic epithelium, constitute one percentage of oral complete ectodermal tumors &9percentage of an odontogenic tumors4. This tumor is benign, which suggests the insidious slowly increase, regionally aggressive having excessive recurrence rate5 Aim: To evaluate radiographical features and root resorption among patients of Ameloblastoma reporting to Dept. of OMFS Study Design: Descriptive Cross-Sectional Study Place and duration of study: Department of Oral and Maxillofacial surgery, Multan Dental College Multan. Duration of this study was 2 years from 1st Jan 2021 to 31th Dec 2022. Methodology: A descriptive audit including all patient records with a histo-pathologically confirmed report of ameloblastoma based on the routine Hematoxylin and Eosin stain. Consecutive non-probability sampling technique was used. Results: One hundred and forty people with an ameloblastoma were contained within ours study amongst whom 45(32.1%) were female and 95(67.9%) were men. 123(87.9%) lesions were found in the mandible. Swelling was mostly told symptoms in 137(97.8%) of all cases. 76(54.3%) showed root resorption. Radiographically, the multilocular appearance accounted for 97(69.3%) while uni-loculancy was present in 43(30.7%) of the lesions. Practical implication: This study help in diagnosis of amelolastoma. This also guides the clinician to differentiate different forms of aelolastoma and differentially diagnose from other radiolucent lesions. Conclusion: This study pointed that ameloblastoma was seen more in men when compared with females Most cases showed root resorption. Mostly ameloblastomas were of multi-locular form/pattern with posterior are of lower jaw as most frequent site involved. Keywords: Ameloblastoma, features, radiolucency & Multi-locular